The treatment of multiple gingival recession defects with connective tissue grafting and enamel matrix derivative in a private practice setting: Two case reports. Issue 4 (25th October 2022) - Scheyer, E. Todd; Gomes, Patricia; Rossi, Andrew
Abstract: Background: Dentofacial esthetics has become a mainstay treatment in periodontics. For a periodontal private practice to succeed in a referral‐based environment, predictability and stability in treatment results are crucial. The scientific literature provides a guide to successfully treating multiple recession defects with non‐carious cervical lesions and lingual recession. These case reports show how the use of biologic mediators, proper case selection, and proper surgical technique may provide a better treatment outcome for our patients. Methods: Two patients with multiple gingival recession defects were treated with autogenous tissue grafting in conjunction with the application of enamel matrix derivative (EMD) to attempt root coverage. Based on the Cairo classification, the recession defects were classified as type I in the maxillary buccal and lingual recession in the mandibular anterior. There were areas of no attached gingiva, loss of enamel, and the presence of non‐carious cervical lesions. Results: At 3‐month post‐treatment in case #1 and 6‐month post‐treatment in case #2, satisfactory esthetic results for the patients and clinician were achieved. These short‐term follow‐ups were favorable for root coverage and soft tissue healing, especially at the 1‐week visit. There was noticeably less edema and erythema. Additionally, dental hypersensitivity was no longer reported for both patients. Conclusion: By using biologic mediators, such as an EMD combined with connective tissue grafting, both multiple recession defects with non‐carious cervical lesions, and lingual recession cases, can be treated successfully in a private practice setting. Using an EMD provides no additional risks to patients, may result in faster healing, and would afford stability of long‐term success by influencing true periodontal regeneration.